Opportunities for household solid waste recycling and policy status in Malaysia - Moh, Yiing Chiee; Abd Manaf, Latifah; Juahir, Hafizan (Springer, 2013)
Malaysia provides ample opportunities for solid waste recycling due to their dependence on recyclable materials, which could be observed from the dominance of recyclables in the wastes disposed at the landfills. This paper attempts to develop an overview on the opportunities for solid waste recycling in Malaysia at the most basic level of a community or nation which is the household unit, besides reviewing on the Malaysian solid waste management and recycling policy status. Information on solid waste recycling is significantly underdeveloped, as most studies tend to focus more on general aspects of solid waste management in Malaysia. Substantial progress has been made by the government and related authorities in developing a more comprehensive solid waste management, recycling policies, awareness campaigns and relevant projects. Waste separation and recycling are part of the major changes in the current policy implementation. However the local participation has not been encouraging and the recycling rate falls back at merely 5 % that proves how uncommon recycling practice is. Households are not aware of proper waste recycling etiquette. Environmental considerations exist among households but space limitations and misconceptions hinder recycling practice. The role of monetary rewards seems to be overplayed and the influence of other reasons for recycling has been slightly underestimated when it comes to implementing recycling policy and programme strategies.